Clinical Sensitivity of Severe Acute Respiratory Syndrome Coronavirus 2 Nucleic Acid Amplification Tests for Diagnosing Coronavirus Disease 2019. (24th July 2020) - Ridgway, Jessica P; Pisano, Jennifer; Landon, Emily; Beavis, Kathleen G; Robicsek, Ari
Abstract: Utilizing 34 348 severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) nucleic acid amplification test (NAAT) results from 2 health systems, we estimated the clinical sensitivity of a single SARS-CoV-2 NAAT. We found that SARS-CoV-2 NAAT has 82%–97% sensitivity for diagnosing coronavirus disease 2019 among symptomatic patients. Abstract : Using severe acute respiratory syndrome coronavirus2 (SARS-CoV-2) nucleic acid amplification test (NAAT) results from two large health systems, this study estimated the clinical sensitivity of a single SARS-CoV-2 NAAT to be 82-97% for diagnosing COVID-19 among symptomatic patients.